The Role of Gynecologic Oncologists in Improving Survival Outcomes of Epithelial Ovarian Cancer: A Retrospective Cohort Study - Hanafy, Widyorini LH; Dwipoyono, Bambang; Adisasmita, Asri C; Regina, Yosephine E; Lians, Airine S; Rahayu, Oktaviani P; Auwelia, Jane G (Kesmas, 2026)
Epithelial ovarian cancer (EOC) is a leading cause of gynecological cancer mortality and is often diagnosed at an advanced stage, resulting in poor survival outcomes. Access to specialized gynecological oncology services has been associated with improved prognosis; however, data on its impact in Indonesia remain limited. This study aimed to evaluate the association between gynecologic oncologist (GO) services and disease-free survival (DFS) in patients with EOC. This retrospective cohort study included 76 patients with EOC who were treated at a national cancer hospital in Jakarta between 2015 and 2018. Patient data were obtained from medical records and followed for three years after the primary treatment. Survival outcomes were analyzed using the Kaplan-Meier curve and Cox proportional hazards model. The overall 3-year DFS rate was 41.6%. Patients treated by GO specialists had a higher DFS rate (54.3%) than those treated in hospitals without GO services (24.5%). Multivariate analysis showed a higher recurrence risk in patients treated without GO services (HR 2.75; 95% CI: 1.32 - 5.74). This study’s findings highlight the potential clinical benefits of facilitating early access to specialized GO care for patients with EOC.